Peran Nilai Perusahaan dalam Memediasi Faktor-faktor yang Mempengaruhi Tax Avoidance di Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia - Tarihoran, Anita (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2024)
This research aims to determine and analyze the factors that influence Tax Avoidance and Firm Value as a mediating variable at non-financial companies listed in Indonesia Stock Exchange for the 2019-2021 period. The population in this research were 679 companies. The sampling method used in this research was purposive sampling and obtained 296 companies as the sample. Analysis of data method used is a quantitative method using a structural equation model with the SmartPLS. The results show that Profitability (ROA), Liquidity (CR), Leverage (DAR) have no effect on Tax Avoidance (ETR) through Firm Value (PBV) at non-financial companies listed in Indonesia Stock Exchange for the 2019-2021 period.